The Relationship between Communication Strategies and Language Proficiency among the English Department Students of IAIN Kudus - Widyaningrum, Leily; Faridi, Abdurrachman; Saleh, Mursid (Universitas Negeri Semarang, 2020)
In foreign language classes, students very often intend to express their ideas to listeners, but they realize that their linguistic or semantic structure is not available, then they give a pause before continuing their utterances. It means that they used communication strategies to close the gap between linguistic competence and communicative competence. Furthermore, many aspects related to the studentsâ€™ communication strategies, one of that is language proficiency. This qualitative case study is set to investigate: (1) the use of communication strategies of students; (2) the language proficiency level of students; (3) the influence of communication strategies to the language proficiency. There are twelve students with high and low proficiency levels as the subject of this research which was taken purposively. They are the second-semester students of the English Education Department at IAIN Kudus in the academic year of 2019/2020. In this study, the researcher used observation, interview, and documentation as the sources of data. It is intended to address the research questions. The results revealed that (1) The students used stalling or time-gaining type and sub-types, namely fillers and self-repetition in which the most popular form of filler was â€œehh, eee, and ehmmâ€; (2) High proficient students were infrequently to produce the error of grammar. While low proficient students often used non-verbal language. It means that students with high proficiency level can process words so that their utterances are more understandable; (3) Communication strategies influenced the language proficiency. It is because high proficient students are able to share their ideas and opinions freely than low proficient students who regularly produce errors of grammar. This study provides valuable contribution in introducing communication strategies and raising studentsâ€™ awareness to actually use English in real-life communication.